Demographic factors affecting technological pedagogical content knowledge in Generation-Z preservice biology teachers - Sudrajat, Ahmad Kamal; Ibrohim, Ibrohim; Susilo, Herawati (Institute of Advanced Engineering and Science, 2024)
Generation-Z dominating preservice biology teachers in this era. Teachers’ TPACK is influenced by factors such as demography. Technological, pedagogical and content knowledge (TPACK) is a framework used in teacher competence in Indonesia. This research will contribute to the training process of Generation-Z preservice biology teachers who have special characteristics. This study aims to determine the effect of demographic factors on the TPACK of Generation-Z preservice biology teachers. A total of 652 Generation Z preservice biology teachers from biggest ten Indonesian educational universities participated in this survey. The research results show that only gender has a relationship with TPACK in every aspect. Motivation to become a teacher influences TPACK, except for the technological knowledge (TK) aspect. In contrast, other aspects do not influence TPACK. Gender and motivation to become a teacher are factors that need attention in the training process for prospective biology teachers. Universities and the government can use these results to formulate suitable training programs for preservice biology teachers in Indonesia.